Implanting Niobium Carbide into Trichoderma Spore Carbon a New Advanced Host for Sulfur Cathodes - Shen, Shenghui (Advanced materials (Deerfield Beach, Fla.), 2019)
© 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.